Middle Palaeolithic raw material procurement and early stage reduction at Jubbah, Saudi Arabia. (March 2017) - Groucutt, Huw S.; Scerri, Eleanor M.L.; Amor, Ken; Shipton, Ceri; Jennings, Richard P.; Parton, Ash; Clark-Balzan, Laine; Alsharekh, Abdullah; Petraglia, Michael D.
Abstract: Several hundred Middle Palaeolithic (MP) archaeological sites have now been identified in the Arabian Peninsula. However, the study of lithic raw material properties and related procurement behaviours is still in its infancy. Here we describe raw material procurement and early stage lithic reduction at MP sites in the Jubbah palaeolake basin, in the Nefud Desert, northern Saudi Arabia. We describe the sites identified during our surveys, and we use petrographic studies to demonstrate that MP assemblages were mostly produced from differing forms of ferruginous quartzite. These raw materials do not substantially vary in composition, although they are not identical in terms of factors such as grain size and the proportion of iron oxide. We then describe the lithic technology at these sites, with a particular focus on the largest assemblage identified, Jebel Katefeh-12 (JKF-12), which provides detailed information on lithic reduction at a quartzite source. Analyses from this site are then considered together with data from other MP sites in the Jubbah basin, where similar raw material was used. The results indicate that factors such as initial clast size/shape and reduction intensity play important roles in influencing aspects of morphological and technological variability. Our results suggest that incursions of MP populations into northern Arabia were probably temporally limited, as might be expected in a marginal and generally arid region. MP raw material procurement sites provide a highly visible signal of these ephemeral incursions, providing information on the ways that human populations adapted to the challenging conditions of the Saharo-Arabian arid belt.